2021
DOI: 10.33425/2768-6647.1004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension Among Adults in Rural Setting in Nigeria: The Need for Paradigm Shift in Prevention and Control

Abstract: Background: Hypertension is a chronic non-communicable medical condition that often leads to complication such as coronary heart disease, renal failure, peripheral vascular disease, retinal hemorrhage and visual impairment, amongst others. It is usually perceived to be more associated with urban/city lifestyle than rural living, but sociodemographic and socio-economic drivers of hypertension in the population are in recent instance generally impactful even in rural setting which can influence changing pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Adebayo et al 38 reported a prevalence rate of 26.4%. Other studies in the countries have reported rates 13.8%-44.5% 15,[40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Adebayo et al 38 reported a prevalence rate of 26.4%. Other studies in the countries have reported rates 13.8%-44.5% 15,[40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%